Influence of sample thickness and cross-sectional area on flexoelectric effect under one-dimensional impact. Issue 1 (4th May 2022) - Hu, Taotao; Li, Yu; Tu, Peng
Abstract: The shock wave generates the strain gradient and consequent electric polarization in samples due to the flexoelectric effect during the impact process. At present, some scholars have studied the influence law of different impact velocities, but the influence of different thickness and cross-sectional area of samples on flexoelectric effect is still blank. In this letter, we have studied the voltage variation of barium titanate samples with different thickness and cross-sectional area under a certain impact velocity. The results show that the maximum voltage value caused by flexoelectric effect increases as the thickness increases, which is basically in positive proportion; it decreases with the increase of diameter, which is in inverse proportion. This research will lay a theoretical foundation for the fabrication of flexoelectricity sensor.